Laser spectroscopic real time measurements of methanogenic activity under simulated Martian subsurface analog conditions - Schirmack, J.; Böhm, M.; Brauer, C.; Löhmannsröben, H.G.; de Vera, Jean Pierre Paul; Möhlmann, D.; Wagner, D. (Planetary and Space Science, 2014)
On Earth, chemolithoautothrophic and anaerobic microorganisms such as methanogenic archaea are regarded as model organisms for possible subsurface life on Mars. For this reason, the methanogenic strain Methanosarcina soligelidi (formerly called Methanosarcina spec. SMA-21), isolated from permafrost-affected soil in northeast Siberia, has been tested under Martian thermo-physicalconditions. In previous studies under simulated Martian conditions, high survival rates of these microorganisms were observed. In our study we present a method to measure methane production as a first attempt to study metabolic activity of methanogenic archaea during simulated conditions approaching conditions of Mars-like environments.To determine methanogenic activity, a measurement technique which is capable to measure the produced methane concentration with high precision and with hightemporal resolution is needed. Although there are several methods to detect methane, only a few fulfill all the needed requirements to work within simulated extraterrestrial environments. We have chosen laser spectroscopy, which is a non-destructive technique that measures the methane concentration without sample taking and also can be run continuously. Inoursimulation, we detected methane production at temperatures down to -5°C, which would be found on Mars either temporarily in the shallow subsurface or continually in the deep subsurface. The pressure of 50kPa which we used in our experiments, corresponds to the expected pressure in the Martian near subsurface. Our new device proved to be fully functional and the results indicate that the possible existence of methanogenic archaea in Martian subsurface habitats can not be ruled out.